(untitled) (Foro de Educacion, 2024)
The call for the decolonization of knowledge refers to both its colonization and contingency and puts the focus on the multiplicity of knowledge. This contradicts European-North-American thinking and definitions of knowledge. Consequently, to advance an epistemological decolonization of knowledge, the actual process of defining knowledge will be analysed and the multiplicity of perspectives stressed at the epistemological level. Using Indian epistemology as an example, I will work out differences in definitions of knowledge and therefore basic diversifications in describing and explaining the emergence of knowledge. Truth-value-neutral forms of knowledge in particular challenge dominant European-North-American philosophical definitions, which incontrovertibly include assumptions of true or false knowledge. An interesting overlap between some Indian epistemologies and postcolonial theories can be observed with regards to the central role of the contextualization of knowledge production and the socially embodied nature of scientific knowledge in general. If the incentives gained are to be taken seriously, the consequences for educational science in general as well as educational practices must be discussed. According to the findings of organizational theory, emphasis on diversification and complication is also seen as an opportunity for the emergence of fresh meaning. Referring to Helen Verran’s concept of generative tension as a sign of collective creativity, encounters between diverse forms of knowledge and epistemological principles are seen as sources of creative processes and prerequisite for the emergence of new positions, perspectives etc., and thus as incubators for innovations.